S-1 maintenance chemotherapy following definitive chemoradiotherapy in high-risk locally advanced nasopharyngeal carcinoma: a propensity score-matched analysis - Zuo, Quan; Jia, Jieqi; Liu, Rong; Zhao, Jingsheng; Wu, Hui; Chen, Jia; Duan, Hexin; Yang, Zaichuan; Shi, Jing; Yang, Qingling; Li, Fanglue; Xiang, Zhibi; et al. (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the efficacy and safety of S-1 maintenance chemotherapy after definitive chemoradiotherapy in patients with high-risk, locally advanced nasopharyngeal carcinoma (NPC).MethodsA total of 536 patients with locally advanced NPC admitted to our hospital between August 2019 and November 2022 were screened. Of these, 171 met the inclusion criteria, including 93 patients who received S-1 maintenance therapy (experimental group) and 78 patients who did not receive maintenance therapy (control group). After 1:1 propensity score matching, 126 patients (63 per group) were finally included in the matched cohort for analysis. All patients received two to three cycles of TPF (paclitaxel liposome, cisplatin, and fluorouracil) neoadjuvant chemotherapy, followed by concurrent chemoradiotherapy within 1–2 weeks later.ResultsFollowing treatment, survival outcomes were assessed. The 3-year progression-free survival rates were 87.3% in the experimental group versus 73.9% in the control group (p = 0.083). The 3-year locoregional recurrence-free survival (LRRFS) rates were 92.7% versus 82.4% (p = 0.277), respectively. The 3-year distant metastasis-free survival (DMFS) rate was significantly higher in the experimental group than in the control group (91.4% vs. 73.9%, p = 0.023). Similarly, the 3-year overall survival (OS) rate was 96.8% versus 82.1% (p = 0.035) in the experimental and control groups, respectively. Subgroup analysis revealed significant DMFS benefits with S-1 maintenance therapy in patients aged <60 years, male patients, those with stage IVa disease, and those with T3–T4 or N2–N3 classification. Additionally, patients who were Epstein-Barr virus (EBV) DNA-negative and those who achieved partial response or stable disease after definitive chemoradiotherapy also showed significant DMFS improvement. Patients with non-keratinizing carcinoma or EBV DNA positivity showed a trend toward improved DMFS as well.Safety:S-1 maintenance chemotherapy demonstrated a favorable safety profile, with only 3.2% of patients experiencing grade 3 adverse events.ConclusionS-1 maintenance chemotherapy after definitive chemoradiotherapy significantly improves DMFS and OS in patients with high-risk locally advanced NPC, with a favorable safety profile.